The presence of eye defects in patients with Turner syndrome is irrespective of their karyotype. (13th May 2015) - Wikiera, Beata; Mulak, Malgorzata; Koltowska‐Haggstrom, Maria; Noczynska, Anna
Summary: Objective: Published data on eye disorders in patients with Turner syndrome (TS) are limited. We aimed to evaluate the prevalence of eye disorders in patients with TS and assess the association with patient karyotype. Design: Cross‐sectional, observational study. Patients: Eighty‐two patients with TS. Measurements: We evaluated visual acuity (distance and proximity), intraocular pressure, optic system refraction, orthoposition, frontal eye segment, the eye fundus and colour vision. For eye fundus abnormalities, we conducted ultrasound examinations, visual field evaluations and fluorescein angiography. We statistically tested the association between the prevalence of eye disorders and karyotype. Results: 50 (61%) patients had monosomy X; 9 (11%) had mosaicism with a normal 46, XX line; 21 (26%) had structural aberrations; and 2 patients (2%) had other chromosomal abnormalities. Eye disorders were diagnosed in 43 (52%) patients, with 29 (35%) patients having multiple eye defects. Defects related to impaired vision were the most common (44%), followed by strabismus (21%), changes in the posterior eye segment (6%), red‐green colour deficiency (5%), changes in the anterior eye segment (5%) and nystagmus (4%). Amblyopia was diagnosed in 13 patients (16%). The most common combinations of ophthalmological defects were hypermetropia and astigmatism with or without other eye problems (12 patients). We found no association between the presence of eye defects and karyotype. Conclusions: Detection of eye abnormalities is necessary in all patients directly after being diagnosed with TS to prevent irreversible deterioration of eye function and permanent poor vision. All girls with TS, irrespective of their karyotype, should be referred to an ophthalmologist.